The effects of tied and untied development loans - Manfred Holthus; Dietrich Kebschull (Intereconomics, 1985)
A decisive change now seems to be occurring in the development practices of the major OECD donor countries. Their own economic objectives are being moved distinctly closer to centre stage. Changes in the instruments of development policy are reputed to generate direct benefits for their own economies. The following article shows that such behaviour is questionable.
Keywords: 330; Development Policy